Temperature Effect on The Tropospheric Radio Signal Strength for UHF Band at Terengganu, Malaysia - Roslan, Umar; Seok, Yew Been; Roshidah, Mat (2016)
In tropospheric layer, radio waves can propagate in a number of different physical mechanisms such as free-space propagation or line-of-sight propagation, reflection, transmission, diffraction, scattering and wave guiding. The constituents in weather such as the wind, air temperature and atmospheric water content may combine in many ways. Certain combinations can cause radio signals to be heard hundreds of miles beyond the ordinary range of radio communications. This study investigates the effect of weather (temperature) on radio wave propagation up to 9GHz. Continuous-wave (CW) envelope fading waveforms were recorded over a period of the one-hour using patch antenna. The observations were conducted at KUSZA Observatory, East Coast Environmental Research Institute (ESERI), UniSZA which is situated in Merang, Terengganu. Spectrum Analyser was used for RFI measurement and weather station for weather effect. The graphs of radio signal attenuation for weather parameter (temperature) against time were plotted. The findings indicate that there is a relationship between radio signals with the change of temperature. The correlation between RFI frequencies and temperature give negative effect for frequency 945 MHz, was r = -0.085, while for 383 MHz (r = 0.249), 1800 MHz (r = 0.268) and 2160 MHz (r = 0.134). These findings will benefit radio wave propagation research field which includes radio astronomy observations, space science, wireless communication, satellite, antenna and mobile communication and also electromagnetic radiation (EMR) research for health.